2018
DOI: 10.13040/ijpsr.0975-8232.9(1).305-12
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Morinda citrifolia L. (Rubeaceae) is a medicinal plant commonly called as Noni. Traditionally the entire plant is used for the treatment of cancer, inflammation, hypertension, diabetes, bacterial infections, and arthritis. The present study aims to explore the antineoplastic activity of Noni Juice (NJ) and Divine Noni Gold (DNG) concentrate on Ehrlich ascites carcinoma (EAC) bearing mice. Antineoplastic activity of NJ and DNG was evaluated in EAC bearing mice by administrating 0.35 ml/mouse p.o. respectively o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 16 publications
2
1
0
Order By: Relevance
“…Additionally, the impairment of renal functions might be due to the direct oxidative renal damaging effect of Cis on the tubular and glomerular structures via the excessive production of free radicals and the depletion of the renal antioxidant defense system [ 17 ], as evidenced in the current study by the observed increase in the renal MDA level and reductions in the GSH content and CAT activity in EAC-bearing mice treated with Cis. These results agreed fully with previous findings of Ali et al [ 49 ] and Longchar and Prasad [ 34 ]. In support of these results, the histopathological and immunohistochemical investigations ascertained the biochemical findings, where some vascular, degenerative, and necrotic changes with only a few neoplastic cells were observed in the renal tissue of EAC-bearing mice treated with Cis, along with weak Ki-67 and strong caspase-3 expressions of neoplastic cells infiltrating the renal capsule.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Additionally, the impairment of renal functions might be due to the direct oxidative renal damaging effect of Cis on the tubular and glomerular structures via the excessive production of free radicals and the depletion of the renal antioxidant defense system [ 17 ], as evidenced in the current study by the observed increase in the renal MDA level and reductions in the GSH content and CAT activity in EAC-bearing mice treated with Cis. These results agreed fully with previous findings of Ali et al [ 49 ] and Longchar and Prasad [ 34 ]. In support of these results, the histopathological and immunohistochemical investigations ascertained the biochemical findings, where some vascular, degenerative, and necrotic changes with only a few neoplastic cells were observed in the renal tissue of EAC-bearing mice treated with Cis, along with weak Ki-67 and strong caspase-3 expressions of neoplastic cells infiltrating the renal capsule.…”
Section: Discussionsupporting
confidence: 93%
“…In support of these results, the histopathological and immunohistochemical investigations ascertained the biochemical findings, where some vascular, degenerative, and necrotic changes with only a few neoplastic cells were observed in the renal tissue of EAC-bearing mice treated with Cis, along with weak Ki-67 and strong caspase-3 expressions of neoplastic cells infiltrating the renal capsule. Similar findings were also observed by Ali et al [ 49 ], Hashem et al [ 17 ], and Longchar and Prasad [ 34 ], indicating the antitumor potency of Cis and its renal damaging adverse side effect.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation